2016
DOI: 10.1159/000452119
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects and Prognostic Factors for Survival in Patients with Recurrent Cervical Cancer after Radical Hysterectomy

Abstract: Background: The aim of this study was to investigate the clinical aspects and prognostic factors for survival in patients with recurrent cervical cancer after radical hysterectomy with node dissection (RHND) for stages IA2-IB1. Patients and Methods: Clinicopathologic characteristics of the primary tumor, pattern of recurrence, method of detection, salvage treatment, and outcome were reviewed from the medical records of patients who underwent RHND between 1987 and 2015. Prognostic factors were identified using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Regarding symptoms at recurrence, the majority of those with recurrence (81.4%) in the current study had symptoms at the diagnosis of recurrence, which is in line with a previous study of early-stage cervical cancer from the same institute, which found more cases of symptomatic (63.1%) than asymptomatic (33.3%) recurrence [16]. In the current study, physical/pelvic examination was able to detect a high percentage of cases of asymptomatic recurrence (44.2%).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding symptoms at recurrence, the majority of those with recurrence (81.4%) in the current study had symptoms at the diagnosis of recurrence, which is in line with a previous study of early-stage cervical cancer from the same institute, which found more cases of symptomatic (63.1%) than asymptomatic (33.3%) recurrence [16]. In the current study, physical/pelvic examination was able to detect a high percentage of cases of asymptomatic recurrence (44.2%).…”
Section: Discussionsupporting
confidence: 92%
“…The impact of earlier diagnosis of late recurrence of cervical cancer on better clinical outcome is beyond the scope or objective of our study. However, we previously reported that symptom status was found to be prognostic factor in recurrent cervical cancer after radical surgery [27]. Thus, surveillance focusing on different target organs by careful physical examination (especially inguinal node palpation) and appropriate investigations such as chest X-ray and bone survey may be necessary additions to a routine surveillance program for patients with clinical findings and/or symptoms of late rec urrence.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment WBC count of >10,000/ μ l without known inflammatory condition or infectious disease was diagnostic for tumor-related leukocytosis. Thrombocytosis was defined as a pretreatment PLT count of >400,000/ μ l without a known inflammatory condition [25].…”
Section: Methodsmentioning
confidence: 99%